2017
DOI: 10.1007/978-1-4939-7465-8_17
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Small-Molecule Ligand Binding to G Protein-Coupled Receptors with Biased or Unbiased Molecular Dynamics Simulations

Abstract: An increasing number of G protein-coupled receptor (GPCR) crystal structures provide important—albeit static—pictures of how small molecules or peptides interact with their receptors. These high-resolution structures represent a tremendous opportunity to apply molecular dynamics (MD) simulations to capture atomic-level dynamical information that is not easy to obtain experimentally. Understanding ligand binding and unbinding processes, as well as the related responses of the receptor, is crucial to the design … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…These results indicated that TCDD has stronger binding affinity towards mVEGFR1 compared to hVEGFR1. Further, crystal structure of mVEGFR1 is not available and only a part of mVEGFR1 as recombinant mouse soluble VEGFR-1 D7 /Fc chimera is available 38,39 . Therefore, we conducted experimental studies followed by molecular dynamic simulations on hVEGFR1.
Figure 3Docking poses of VEGFR1 interaction with the TCDD.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that TCDD has stronger binding affinity towards mVEGFR1 compared to hVEGFR1. Further, crystal structure of mVEGFR1 is not available and only a part of mVEGFR1 as recombinant mouse soluble VEGFR-1 D7 /Fc chimera is available 38,39 . Therefore, we conducted experimental studies followed by molecular dynamic simulations on hVEGFR1.
Figure 3Docking poses of VEGFR1 interaction with the TCDD.
…”
Section: Resultsmentioning
confidence: 99%
“…Understanding the binding of a ligand typically to a substrate or a regulator is a dynamic process and is key in understanding the function itself 32 . MDS has been used successfully in elucidating ligand-induced perturbations in several studies reported previously 3539 . In the present study, to analyse the conformational changes between hVEGFR1 and hVEGFR1-TCDD complexes, we performed MDS.…”
Section: Resultsmentioning
confidence: 99%
“…Computational and simulation methods can play useful roles in drug discovery as well. These methods have helped improve our understanding of GPCRs' structures and functions [2,[46][47][48][49]. There are three main requirements for an MD simulation: the model system, the force field, and the MD simulation software.…”
Section: New Insights From Molecular Dynamics Simulationsmentioning
confidence: 99%
“…As of February 2019, there are 59 unique receptor structures solved (https://gpcrdb.org/structure/statistics), most of them corresponding to the rhodopsin (or class A) family (Figure 1). Molecular dynamics (MD) simulations started from these experimental structures have provided very important insights into ligand binding and receptor activation (Miao and McCammon, 2016; Sengupta et al, 2016; Latorraca et al, 2017; Marino and Filizola, 2018; Torrens-Fontanals et al, 2018; Velgy et al, 2018).…”
Section: Introductionmentioning
confidence: 99%